2019
DOI: 10.1016/j.pediatrneurol.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Family History Variables Associated With Neurological and Cognitive Development in Sturge-Weber Syndrome

Abstract: Background: Sturge-Weber syndrome (SWS) is caused by a somatic mutation in GNAQ leading to capillary venous malformations in the brain presenting with various neurological, ophthalmic, and cognitive symptoms of variable severity. This clinical variability makes accurate prognosis difficult. We hypothesized that the greater extent of physical factors (extent of skin, eye, and brain involvement), presence of possible genetic factors (gender and family history), and age of seizure onset may be associated with gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 22 publications
(28 reference statements)
2
34
1
Order By: Relevance
“…A family history of seizures or epilepsy is associated with an early age of seizure onset in SWS. 136 This suggests that genetic factors, beyond the underlying somatic mutation in GNAQ , have a role in determining the timing of seizure onset in SWS. 1 The extent of skin involvement with PBW may also be a prognostic factor.…”
Section: Discussion and Desseminationmentioning
confidence: 99%
See 1 more Smart Citation
“…A family history of seizures or epilepsy is associated with an early age of seizure onset in SWS. 136 This suggests that genetic factors, beyond the underlying somatic mutation in GNAQ , have a role in determining the timing of seizure onset in SWS. 1 The extent of skin involvement with PBW may also be a prognostic factor.…”
Section: Discussion and Desseminationmentioning
confidence: 99%
“…Whether gender impacts the early evolution of SWS as manifested in neuroimaging remains to be studied. A family history of seizures or epilepsy is associated with an early age of seizure onset in SWS 136. This suggests that genetic factors, beyond the underlying somatic mutation in GNAQ , have a role in determining the timing of seizure onset in SWS 1.…”
Section: Discussion and Desseminationmentioning
confidence: 99%
“…According to Day et al .,[ 3 ] the children with worst prognostic factors with SWS brain and skin involvement should be managed to prevent seizures and stroke. According to Comi,[ 4 ] continued safe screening methods should be utilized to detect presymptomatic brain and eye involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The largest study on SWS to date found that males with SWS that experienced seizure onset at age less than or equal to 6 months were more likely to experience stroke-like episodes. 16 Sex-related differences have been extensively studied outside the SWS literature. In terms of stroke, males are more likely to experience ischemic episodes at a younger age.…”
Section: Discussionmentioning
confidence: 99%